Academic Burnout, Mindfulness and Psychological Well-being in Young Adults - Tanveer, Zainab; Kamran, Fatima (Annals of Human and Social Sciences, 2023)
Academic Burnout is part of student life, and it affects the psychological well-being of young adults. Mindfulness acts as a buffer against negative effect of academic burnout on young adults’ psychological well-being. The present study was designed to examine the relationship between academic burnout, mindfulness, and psychological well-being in young adults. A sample of 200 students was taken from different colleges and universities of Punjab, Pakistan. Copenhagen Burnout Inventory, Mindful Attention Awareness Scale, and Psychological Well-being Scale were used as assessment measures. A correlation research design with a purposive sampling strategy has been used. Results revealed that academic burnout and mindfulness has significant positive relationship with each other. Classmate related burnout significantly predict psychological well-being in young adults and mindfulness does not mediate the relationship between academic burnout and psychological well-being. It was concluded that classmate related burnout has a great impact on psychological well-being.